2023
DOI: 10.1088/2051-672x/acd70a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contact angle on droplet parameters in ellipsoidal wettability model

Abstract: Contact angle is one of the most important indexes to evaluate the hydrophobicity of solid surface. In order to explore the wetting characteristics of droplets on anisotropic solid surfaces, including contact angle, droplet radius, droplet height, contact radius, contact area and projected area, an ellipsoidal droplet contact angle model was established. By collecting the droplet size parameters of FKM prepared by template method, the correctness of the theoretical model was verified. Among them, the maximum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The contact angle of polysaccharide films containing enzymes can be significantly influenced by various factors, such as ultraviolet (UV) radiation. UV irradiation can alter the contact angle and surface properties of biopolymeric films, leading to changes in surface roughness and polarity [53]. Furthermore, Zimoch-Korzycka et al [54] reported that the presence of enzymes such as cellulase in polysaccharide films can impact their physicochemical stability over time, affecting parameters such as water vapor permeability and tensile strength.…”
Section: Contact Angle Before and After Ultraviolet Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle of polysaccharide films containing enzymes can be significantly influenced by various factors, such as ultraviolet (UV) radiation. UV irradiation can alter the contact angle and surface properties of biopolymeric films, leading to changes in surface roughness and polarity [53]. Furthermore, Zimoch-Korzycka et al [54] reported that the presence of enzymes such as cellulase in polysaccharide films can impact their physicochemical stability over time, affecting parameters such as water vapor permeability and tensile strength.…”
Section: Contact Angle Before and After Ultraviolet Radiationmentioning
confidence: 99%
“…Furthermore, Zimoch-Korzycka et al [54] reported that the presence of enzymes such as cellulase in polysaccharide films can impact their physicochemical stability over time, affecting parameters such as water vapor permeability and tensile strength. Xu et al [53] found that UV irradiation exposure decreases water contact angles in certain polymer films, attributed to the formation and release of surfactants from irradiated surfaces.…”
Section: Contact Angle Before and After Ultraviolet Radiationmentioning
confidence: 99%